(untitled) (Bangladesh Journal of Agricultural Research, 2015)
Climate change is expected to intensify existing problems and create new combinations of risks, particularly in Africa. The situation is made worst due to factor such as widespread poverty, over dependence on rain fed agriculture, inequitable land distribution, limited access to capital and technology, inadequate public infrastructure, such as roads, long term weather forecasts and inadequate research and extension. By lessening the severity of key damages to the agricultural sector, adaptation is the key defensive measure. Adaptation to climate change involves changes in agricultural management practices in response to changes in climate conditions. This paper reviews agricultural adaptation strategies employed by farmers in various countries in Africa in cushioning the effects of climate change. The common agricultural adaptation strategies used by farmers were the use of drought resistant varieties of crops, crop diversification, changes in cropping pattern and calendar of planting, conserving soil moisture through appropriate tillage methods, improving irrigation efficiency, and afforestation and agro-forestry. The paper concluded that improving and strengthening human capital through education, outreach programmes, extension services at all levels will improve capacity to adapt to climate change impact. DOI: http://dx.doi.org/10.3329/bjar.v39i3.21984 Bangladesh J. Agril. Res. 39(3): 407-418, September 2014